PENGARUH GAYA KEPEMIMPINAN TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI PEMERINTAH DAERAH - lili indrawati; Etti Ernita Sembiring (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2020)
The purpose of this research is to analyze and prove the role of leadership style against employee productivity in local government.The research was carried out at the Bandung Local Government. The number of respondent was 4 persons each from 27entity from West Bandung Local Government. The entity which are used as sample in this research are finance office. Regression is used to analyze the data from the respondent.The research shows that leadership style does affect positive significantly the employee productivity of local government. Keyword:Leadership Style, Employee Productivity, Local Government.